Incidental Bladder Cancer Detected on Multiparametric Magnetic Resonance Imaging of the Prostate Gland - Al Sardari; John V. Thomas; Jeffrey W. Nix; Jason A. Pietryga; Rupan Sanyal; Jennifer B. Gordetsky; Soroush Rais-Bahrami (Case Reports in Urology)
The increased use of axial imaging in various fields of medicine has led to an increased frequency of incidental findings, specifically incidental cancer lesions. Hence, as the use of multiparametric magnetic resonance imaging (MP-MRI) for prostate cancer detection, staging, and management becomes more widespread, the potential for additional incidental findings in the pelvis increases. Herein, we report the case of a man on active surveillance for low-grade, early-staged prostate cancer who underwent MP-MRI and was incidentally found to have a high-grade bladder cancer lesion.